2019
DOI: 10.1007/s12325-019-01157-4
|View full text |Cite
|
Sign up to set email alerts
|

Matching-Adjusted Indirect Comparison of Health-Related Quality of Life and Adverse Events of Apalutamide Versus Enzalutamide in Non-Metastatic Castration-Resistant Prostate Cancer

Abstract: Introduction: The present study aimed to indirectly compare apalutamide and enzalutamide with respect to tolerability and healthrelated quality of life (HRQoL) among men with non-metastatic castration-resistant prostate cancer (nmCRPC). Methods: Patient-level data from the SPARTAN study [apalutamide ? androgen deprivation therapy (ADT) versus placebo ? ADT] and aggregate published data from the PROSPER study (enzalutamide ? ADT versus placebo ? Enhanced Digital Features To view enhanced digital features for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…In the PROSPER trial, Enzalutamide showed to increase the time to deterioration in HRQoL, when compared with placebo ( 25 ). According to a recent anchored matching-adjusted indirect comparison (MAIC) study, the probability of a better HRQoL with Apalutamide versus Enzalutamide was 73.1% ( 26 ). Data from the primary analysis of ARAMIS trial revealed similar QoL scores between Darolutamide and placebo groups, with scores consistently favoring Darolutamide - yet the clinically meaningful thresholds were not reached ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the PROSPER trial, Enzalutamide showed to increase the time to deterioration in HRQoL, when compared with placebo ( 25 ). According to a recent anchored matching-adjusted indirect comparison (MAIC) study, the probability of a better HRQoL with Apalutamide versus Enzalutamide was 73.1% ( 26 ). Data from the primary analysis of ARAMIS trial revealed similar QoL scores between Darolutamide and placebo groups, with scores consistently favoring Darolutamide - yet the clinically meaningful thresholds were not reached ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment landscape for HCC is expanding rapidly, and there is a resultant need for head-to-head clinical trial data to guide second-line HCC treatment decisions. In this setting, indirect treatment comparisons offer standardized methods for generating comparative estimates that are widely accepted for health technology assessment [ 24 , 25 ] and are increasingly recognized in the clinical sphere for their potential to guide clinicians in their decision-making [ 27 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…While MAIC procedures can reduce the impact of potentially effect-modifying baseline characteristics for reported covariates, they were not able to adjust for between-trial differences in assessment schedules or for the presence of sorafenib-intolerant patients in the CELESTIAL population (versus their exclusion from RESORCE). Such differences are unavoidable features of some indirect treatment comparisons [ 27 , 28 ] and network meta-analyses [ 38 , 39 ], but are relevant factors to consider when interpreting their results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the matchingadjusted indirect comparison method, we found that the incidence of fatigue [p (OR <1) = 99.5%], hypertension [p (OR <1) = 99.2%], headache [p (OR <1) = 86.7%], nausea [P (or <1) = 80.0%], and loss of appetite [p (OR <1) = 98.3%] in the apalutamide group was significantly lower than that in the enzalutamid group. Apalutamide treatment decreased the incidence of adverse events and serious adverse events by 66.9% and 90.9%, respectively, patients administered with apalutamide had a higher tolerance toward nmCRCP treatment [22]. However, patients who received apalutamide were more likely to develop multiple sclerosis and osteoarthritis than those who received enzalutamid [23].…”
Section: Apalutamidementioning
confidence: 94%